Answer:
(x+3)²=16
Explanation:
I'm gonna solve this equation by completing the square
x²+6x-7 = 0 by Completing The Square
Add 7 to both side of the equation :
x²+6x = 7
Now you take the coefficient of x , which is 6 , divide it by two = 3 , and finally square it giving 9
Add 9 to both sides of the equation :
x²+6x+9=7+9
(x+3)x(x+3)=(x+3)²
7+9=16
---------------
| (x+3)²=16 |
---------------
Now you square root both sides to get x+3=±4
x+3=+4 or x+3=-4
-------------------------------
x+3=+4= -7
x+3=-4= 1
-------------------------------
x= -7
x= 1
Hope this helps! Have an amazing day :)